Analysis of the margins of merchandising and the fairness of the trade of the palm oil in the Haut-Uele province, in DR Congo - SHINDANO, Jean-Claude; Leonard MUANASAKA KABUITA,; Prosper SENGI BANGAMA,; Samuel MOLANDAY, (IJRDO - Journal of Business Management, 2019)
The objective of this study is to contribute to the improvement of the performance of the merchandising of the palm oil in the province of the Haut-Uele, in DRC. The analysis was about the margins of merchandising and the fairness of the trade of the palm oil. To arrive there, 180 people (producers, retailers, depositories, kadhahuiles, tradesmen and exporters) have been investigated in the six territories of the Haut-Uele Province. The studied parameters were relative to the prices of purchase and sale, to the committed costs, to the constraints of merchandising of the palm oil in the region, the margins of merchandising. The results showed that the clean margins vary from an actor to another  between  2.884,05 FC (at the depository) and 5.827,50 FC (at the exporter) for the can of 24 liters and a territory to another (2.167,77 FC in Niangara and 6.252,23 FC in Watsa). Besides, all values of the fairness of the trade of the palm oil are so much positive among all intervening parties that in all territories varying between 1,26 and 122,70. The trade of the palm oil in this province is therefore beneficial among all traders but is not equitable.  The problems of road infrastructures, of insecurity in the territories to the North of the province (Dungu and Faradje), the various harassments to the countless barriers erected in the road in the Haut-Uele Province, etc., are the basis of the observed differences margins between the actors, and also between the territories.